Socialization of Growth and Development Stimulation of Toddlers in Posyandu Cadres in Mulyasari Village in the Working Area of Tamansari Health Center - Sri Mulyanti; Hani Handayani; Winda Windiani; Tatang Kusmana; Heri Budiawan (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The Stimulation Detection and Early Intervention of Growth and Development (SDIDTK) program is one of the main programs of the puskesmas. Several efforts can be made to help children grow and develop optimally. Posyandu as a form of community participation under the Ministry of Health is one of the most basic levels of implementation of public health education and monitoring. The liveliness of posyandu activities is based on the participation of posyandu cadres. The task of posyandu cadres is very important and complex where posyandu activities should not only monitor growth but also monitor development so that early growth and development deviations can be detected. The main problem that is prioritized is the lack of optimal cadres in stimulating the growth and development of toddlers early. Provide assistance to partners, namely posyandu cadres, by providing counseling / health education about toddler growth and development. And socialization of cadres with role play and demonstration media using growth and development assessment sheets (KPSP) directly, this can increase the understanding of cadres in assessing or measuring toddler growth and development. As well as providing training to posyandu cadres as a whole in early detection of toddler growth and development until cadres are able to assess obstacles to toddler growth and development. The output targets of this community service are publications in accredited national journals, publishing articles in mass media, making videos of activities uploaded to YouTube, increasing the knowledge and skills of cadres.